Metabolic profiling and pharmacokinetic studies of Baihu-Guizhi decoction in rats by UFLC-Q-TOF-MS/MS and UHPLC-Q-TRAP-MS/MS - Yan He; Zhenkun Zhou; Weijie Li; Yanqiong Zhang; Ruoyao Shi; Tao Li; Linlin Jin; Hongliang Yao; Na Lin; Hao Wu (BMC, 2022)
Abstract Background Baihu-Guizhi decoction (BHGZD) is a well-documented traditional Chinese Medicine (TCM) prescription that has been extensively applied to treating rheumatoid arthritis. Despite of its beneficial outcomes, the chemical constituents of BHGZD have not been fully portrayed and the in vivo absorption, distribution, metabolism, and excretion (ADME) patterns of absorbed components have never been described. Methods Characterization of absorbed components and in vivo biotransformation profiling of these feature compounds were based on the ultra-fast liquid chromatography-quadrupole-time-of-flight tandem mass spectrometry (UFLC-Q-TOF-MS/MS). Furthermore, the ultra-high-performance liquid chromatography tandem ion trap quadrupole mass spectrometry (UHPLC-Q-TRAP-MS/MS) system were performed to investigate the pharmacokinetics of active ingredients from BHGZD. Results In this study, we have identified and tentatively characterized 18 feature absorbed prototype and 15 metabolites of BHGZD in rat serum and the in vivo transformation pathways of these absorbed constituents were proposed. Besides, we have established novel quantitative methodology of five crucial components of BHGZD and have monitored the pharmacokinetic behaviors of these constituents spontaneously in rat serum after BHGZD gavage. After rats received two ways of BHGZD gavage, the pharmacokinetic behaviors of each compound exhibited relatively similar behaviors, as evidenced by similar curve track as well as relatively close time to reach maximum concentration (Tmax) and half washout time (T1/2). Whereas the maximum plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC) values of five analytes with multiple dosage were a bit higher than single dosage. Conclusion This study added knowledge into the material basis and bio-transformation patterns of BHGZD in vivo, which would be of great value for exploring pharmacological effects and mechanism of BHGZD.